Weak associations between personality and contraceptive choice - Pletzer, Belinda; Lang, Carmen; Derntl, Birgit; Griksiene, Ramune (Frontiers in Neuroscience, 2022)
Prospective randomized controlled trials on hormonal contraceptive (HC) effects on the brain are rare due to a number of methodological challenges. Thus, much of the evidence on HC effects on the brain comes from cross-sectional studies comparing HC-users to non-users. In interpreting these findings, it is of importance to be aware of potential confounds associated with women’s contraceptive choices. Previous studies have discussed age, education, social status, sexual orientation, relationship status, and tolerability of HC. Given the current trend toward a reduction in HC use and increased skepticism toward HC it seems relevant to also identify variables associated with women’s attitudes toward HC and whether they may represent confounds for neuroscientific studies. In the present study, we investigated whether women’s personality characteristics were associated with their choice to use or not use HC in the present, past and future and the type of HC chosen. 1,391 females aged 18–45 years participated in an online survey including the HEXACO-60 personality questionnaire, as well as two different measures of gender role, and provided information about their current and previous contraceptive status, as well as experiences with and attitudes toward contraceptive use. We compared (i) current, previous and never-users of HC, (ii) prospective users of HC to women who opposed future HC use, and (iii) current users of IUDs to current users of oral contraceptives. Results revealed that associations between personality and the decision to use or not use HC were negligible, while differences in personality were observed corresponding to contraceptive type. Current users of IUDs showed higher agreeableness and extraversion compared to current users of oral contraceptives. The results suggest that personality is more strongly associated to the choice of contraceptive type rather than the choice between hormonal and non-hormonal options.